PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DALAM MENINGKATKAN HASIL BELAJAR DI UPTD SMPN 2 SABBANGPARU - Nasriadi, Muhammad; Anwar, Yunus; Surani; Nurlaelah; Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the application of the Think Pair Share (TPS) cooperative learning model and the improvement of student learning outcomes after the model is applied to Islamic Religious Education (PAI) subjects. This study uses Classroom Action Research (CAR) which is carried out in two cycles, where each cycle consists of planning, action implementation, observation, and reflection. The subjects of the study were 27 students of class VIII.2 UPTD SMP Negeri 2 Sabbangparu, Wajo Regency. Data collection techniques were carried out through observation, tests, and documentation. Data were analyzed using quantitative and qualitative approaches to determine the improvement in learning outcomes and student activities during the learning process. The results of the study indicate that the application of the Think Pair Share (TPS) cooperative learning model is able to significantly improve student learning outcomes. In the initial conditions, only 29.63% of students achieved learning mastery. After the implementation of the TPS model in cycle I, the percentage of completion increased to 66.66%, then increased again in cycle II to 92.59%, thus achieving the set classical completion, which is ≥75%. In addition to improving learning outcomes, student activity in the learning process also experienced good development. Students appeared more active in independent thinking (think), discussing with partners (pair), and presenting discussion results in front of the class (share). Thus, it can be concluded that the cooperative learning model of the Think Pair Share (TPS) type is effective in improving learning outcomes and student activity in Islamic Religious Education (PAI) subjects.